Hubungan Antara Obesitas Sebagai Faktor Risiko Osteoarthritis Lutut Dengan Aktivitas Fungsional - Utami, Mayang Sri; , Umi Budi Rahayu, S.Fis.,Ftr.,M.Kes; , Wahyuni, S.Fis.,Ftr.,M.Kes (2015)
Osteoarthritis (OA) is a chronic disease which is difficult to find the significant cause. It is characterized by the loss of joint cartilage in stages. The main abnormalities in OA cartilage is the damage which is followed by the thickening of subchondral bone, osteophytes growth, ligament damage and mild inflammation of the synovium, so that the relevant joint create efusi. Some factors which have been studied as a risk factor of OA knee include obesity, workload, and trauma. Obesity is the strongest factor causing OA knee. Obesity is a multifactorial disease caused by excessive accumulation of fat tissue, which lead to impair health. The problem posed is pain, limited range of motion (LGS), decreased muscle strength, flexibility disorder, disturbance stability, reduction of muscle mass (atrophy) that interfere functional activities. This study aimed to investigate the relationship of obesity as a risk factor of knee osteoarthritis toward functional activity. This research done at Moeslem gathering of Sunday Pahing at Teggalan Wironanggan, Gatak Sukaharjo on December 14, 2014. This research method applied cross sectional observation approach with the total sample of 85 people and among those samples, 40 people had met the inclusion criteria DAK exclusion. The data obtained are not normally distributed; statistical test was done by using Chi Square test. The results based on data analysis done by using Chi Square test showed that the value of p = 0.001, or the value of p <0.05 means Ho is rejected and Ha is accepted. It is concluded that there is a relationship of obesity as a risk factor of knee osteoarthritis toward functional activity. Hopefully this research can provide more information for the public, especially patients with knee osteoarthritis problem to avoid disability.